2023
DOI: 10.1108/jhom-02-2022-0053
|View full text |Cite
|
Sign up to set email alerts
|

Exploring perceived barriers for advancement to leadership positions in healthcare: a thematic synthesis of women's experiences

Abstract: PurposeThis paper aims to explore the voices of women describing the perceived barriers for advancing to leadership positions in healthcare.Design/methodology/approachA systematic search was conducted through Elton B Stephans Company (EBSCO) host research platform using the databases Cumulative Index to Nursing and Allied Health Literature (CINAHL) Complete, Medical Literature Analysis and Retrieval System Online (MEDLINE) Complete and American Psychological Association (APA) PsycInfo. Nine papers were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The lack of women in high-level leadership positions as role models is a recognized barrier to pursuing leadership. 14 To help address this problem, the ECWLP incorporated numerous opportunities for participants to meet and connect with leaders in the Dean’s office and C-suite, professors, and women with endowed chairs. We wanted the early career women to see themselves represented in spaces they had not previously considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The lack of women in high-level leadership positions as role models is a recognized barrier to pursuing leadership. 14 To help address this problem, the ECWLP incorporated numerous opportunities for participants to meet and connect with leaders in the Dean’s office and C-suite, professors, and women with endowed chairs. We wanted the early career women to see themselves represented in spaces they had not previously considered.…”
Section: Discussionmentioning
confidence: 99%
“…Additional obstacles for women that have been noted in other studies include salary inequity, lack of diversity in leadership, stereotypes, gender bias and discrimination, home and family responsibilities, and lack of confidence. 14 , 15 , 41 , 42 Leadership programs alone cannot overcome these barriers. Achieving gender equity in leadership will require dedicated effort by institutional leadership nationwide to meaningfully improve systems and culture at work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings in this theme largely support previous research. For instance, Haines and McKeown (2023) explored the perceived obstacles women face in healthcare leadership and found that work-life balance and the impact on family and children were major challenges. Young et al (2023) examined the work-life balance and influence of occupational characteristics of information technology professionals and found that women were more likely than men to align occupational commitment to work-life balance with its implications for the family.…”
Section: Theme 3: the Impact On Childrenmentioning
confidence: 99%